The Role Of Fronliner Aston Jember Hotel Conference Center In Improving Guest Satisfaction : Case Study In The Front Office Department - Dilza Fardana Rinda; Faozen Faozen (Empat Sembilan Publisher, 2024)
This study examines the important role of frontliners at Aston Jember Hotel & Conference Center in improving guest satisfaction. Frontliners, including receptionists, reservation staff, guest service agents, and other front office staff, have a central role in shaping the guest experience from check-in to check-out. This study aims to identify the specific duties and responsibilities of frontliners as well as how their performance affects guest satisfaction. Data were collected through a mixed method approach, using qualitative and quantitative data. Quantitative data was obtained through guest satisfaction surveys, while qualitative insights were obtained from interviews with guests and front office staff. The findings show that the effectiveness of frontliners in providing warm welcomes, efficient communication, professional complaint handling, and personalized service significantly contribute to a positive guest experience. In addition, the frontliner's ability to collaborate well with other departments and maintain a high standard of professionalism further increases guest satisfaction. The study emphasizes the importance of ongoing training for frontliners to equip them with the necessary skills to meet and exceed guest expectations. The results show that by investing in the development and support of frontliners, hotels can significantly improve guest satisfaction, which in turn can increase guest loyalty and strengthen the hotel's reputation in the competitive hospitality market. Further research is suggested to explore the impact of technological advancements on the role of frontliners and conduct comparative studies across different hotel categories to identify best practices in guest service management.